A Metabolomic Analysis of Sensitivity and Specificity of 23 Previously Proposed Biomarkers for Renal Transporter-Mediated Drug-Drug Interactions - Geßner, Arne; Müller, Fabian; Wenisch, Pia; Heinrich, Markus; König, Jörg; Stopfer, Peter; Fromm, Martin (Clinical Pharmacology & Therapeutics, 2023)
Endogenous biomarkers are discussed as tools for detection of drug-drug interactions (DDIs) mediated by renal transport proteins, such as organic cation transporter 2 (OCT2), multidrug and toxin extrusion proteins (MATE1 and MATE2-K) and organic anion transporters (OAT1 and OAT3). Whereas sensitivity of some endogenous biomarkers against at least one clinical transporter inhibitor has frequently been shown, intra-study comparisons of the extent of effects of inhibitors on different biomarkers are frequently lacking. Moreover, in vivo specificity of such discussed biomarkers has frequently not been studied. We therefore investigated changes of 10 previously described putative biomarkers for inhibition of OCT2/MATEs, as well as 15 previously described putative biomarkers for OATs in human plasma and urine samples of healthy volunteers in response to treatment with 4 inhibitors of transport proteins [verapamil (P-glycoprotein), rifampin (organic anion transporting polypeptides), cimetidine (OCT2/MATEs), and probenecid (OATs)]. Two of the putative biomarkers had been suggested for both OCT2/MATEs and OATs. All substances were unequivocally identified in an untargeted metabolomics assay. The OCT2/MATE biomarkers choline and trimethylamine N-oxide were both sensitive and specific (median log2-fold changes −1.18 in estimated renal elimination and −0.85 in urinary excretion, respectively). For renal OATs, indoleacetyl glutamine and indoleacetic acid (median log2-fold changes −3.77 and −2.85 in estimated renal elimination, respectively) were the candidates for sensitive and specific biomarkers with the most extensive change, followed by taurine, indolelactic acid, and hypoxanthine. This comprehensive study adds further knowledge on sensitivity and specificity of 23 previously described biomarkers of renal OCT2/MATE- and OAT-mediated DDIs.
CRIS-Team Scopus Importer:2023-10-27

Analysis of amino acid residues in the predicted transmembrane pore influencing transport kinetics of the hepatic drug transporter organic anion transporting polypeptide 1B1 (OATP1B1) - Gruetz, Moritz; Sticht, Heinrich; Gläser, Hartmut; Fromm, Martin; König, Jörg (BBA - Biochimica et Biophysica Acta, 2016)
The hepatic uptake transporters OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) mediate the uptake of endogenous metabolites and drugs from blood into hepatocytes. Alterations of transport function are accompanied with variations in drug plasma concentrations and the risk of adverse drug effects. Thus, knowledge on amino acids determining substrate recognition or transport kinetics are important to predict alterations in transport kinetics. Therefore, we analyzed the charged amino acids His54 and Tyr169, both located at the extracellular entry of the predicted transmembrane pore of OATP1B1. Based on a computational analysis we established HEK293 cell lines overexpressing the mutant OATP1B1 proteins HEK-OATP1B1p.H54Q, -p.H54A, -p.Y169H and -p.Y169A and analyzed protein expression, localization and transport kinetics of the four OATP1B1 substrates bromosulfophthalein, estradiaol-17?-glucuronide, taurocholate and pravastatin. Consequences on transport were detected for all mutants and these were different for each amino acid exchange and for each substrate tested. For example, the exchange H54Q resulted in reduced transport for BSP (78% of wildtype OATP1B1 transport at 0.05?M, P<0.01) with reduced affinity to this substrate (Km value increases from 0.76?M to 8.04?M) but in stimulated E217?G transport (138% compared to wildtype transport at 10?M, P<0.001). Investigating amino acid exchanges located at the extracellular entry of the transport pore of the OATP1B1 protein we demonstrated that these residues are involved in modulating transport kinetics and this participation strongly depends on the substrate and not on the physicochemical character of the investigated amino acid.
EVALuna2:8698

Analysis of naturally occurring mutations in the human uptake transporter NaCT important for bone and brain development and energy metabolism - Selch, Stefan; Chafai, Anja; Sticht, Heinrich; Birkenfeld, Andreas L.; Fromm, Martin; König, Jörg (Scientific Reports, 2018)
The human uptake transporter NaCT is important for human brain development, brain function and energy metabolism and mediates the uptake of citrate and other intermediates of the tricarboxylic acid cycle from blood into neurons and hepatocytes. Mutations in the SLC13A5 gene encoding NaCT are associated with epileptic encephalopathy. To gain more insights into the transport mechanisms we analyzed the functional consequences of mutations in the SLC13A5 gene on NaCT-mediated transport function. Using HEK293 cells expressing wild-type and eight mutated NaCT proteins, we investigated the mRNA and protein amount as well as the protein localization of all NaCT variants. Furthermore, the impact on NaCT-mediated citrate uptake was measured. In addition, a structural model of the transport pore was generated to rationalize the consequences of the mutations on a structural basis. We demonstrated that all proteins were synthesized with an identical molecular weight as the wild-type transporter but several mutations (NaCTp.G219R, -p.G219E, -p.T227M, -p.L420P and -p.L488P) lead to a complete loss of NaCT-mediated citrate transport. This loss of transport activity can be explained on the basis of the developed structural model. This model may help in the further elucidation of the transport mechanism of this important uptake transporter.
EVALuna2:34652

A Novel and Cross-Species Active Mammalian INDY (NaCT) Inhibitor Ameliorates Hepatic Steatosis in Mice with Diet-Induced Obesity - Zahn, Grit; Willmes, Diana M.; El-Agroudy, Nermeen N.; Yarnold, Christopher; Jarjes-Pike, Richard; Schaertl, Sabine; Schreiter, Kay; Gehrmann, Wiebke; Wong, Andrea Kuan Cie; Zordan, Tommaso; König, Jörg; Jordan, Jens; et al. (Metabolites, 2022)
Mammalian INDY (mINDY, NaCT, gene symbol SLC13A5) is a potential target for the treatment of metabolically associated fatty liver disease (MAFLD). This study evaluated the effects of a selective, cross-species active, non-competitive, non-substrate-like inhibitor of NaCT. First, the small molecule inhibitor ETG-5773 was evaluated for citrate and succinate uptake and fatty acid synthesis in cell lines expressing both human NaCT and mouse Nact. Once its suitability was established, the inhibitor was evaluated in a diet-induced obesity (DIO) mouse model. DIO mice treated with 15 mg/kg compound ETG-5773 twice daily for 28 days had reduced body weight, fasting blood glucose, and insulin, and improved glucose tolerance. Liver triglycerides were significantly reduced, and body composition was improved by reducing fat mass, supported by a significant reduction in the expression of genes for lipogenesis such as SREBF1 and SCD1. Most of these effects were also evident after a seven-day treatment with the same dose. Further mechanistic investigation in the seven-day study showed increased plasma beta-hydroxybutyrate and activated hepatic adenosine monophosphate-activated protein kinase (AMPK), reflecting findings from Indy (- / -) knockout mice. These results suggest that the inhibitor ETG-5773 blocked citrate uptake mediated by mouse and human NaCT to reduce liver steatosis and body fat and improve glucose regulation, proving the concept of NaCT inhibition as a future liver treatment for MAFLD.
CRIS-Team WoS Importer:2022-09-09

Assays for Analyzing the Role of Transport Proteins in the Uptake and the Vectorial Transport of Substances Affecting Cell Viability - Taghikhani, Emir Puyan; Fromm, Martin; König, Jörg (Methods in Molecular Biology, 2017)
Endogenous compounds, drugs, or other xenobiotics may affect cell viability. A prerequisite for intracellular cell damage is the uptake of such substances across the plasma membrane into cells. Furthermore, the subsequent transporter-mediated export out of cells may influence cell viability. Therefore, transport proteins mediating the uptake (uptake transporter) or export (export pumps) of substances in and out of cells are important determinants of cell viability. Uptake transporters mostly belong to the superfamily of solute carriers (SLC transporters), whereas export pumps are members of the ABC-transporter superfamily (ATP-binding cassette). Cell systems recombinantly overexpressing uptake transporters (single transfectants) or multiple-transfected cell models expressing simultaneously an uptake transporter together with an export pump (double transfectants) are important in vitro tools for analyzing protein-mediated transport of potentially cell toxic compounds.Here we describe different in vitro transport assays for the functional analysis of transport proteins. Using single-transfected HEK293 cells stably overexpressing an uptake transporter, substances can be tested as potential substrates (uptake assay) or potential transport inhibitors (inhibition assay) for the respective transport protein. Vectorial transport of substances with the uptake across the basolateral plasma membrane and the export across the apical membrane of polarized grown MDCKII cells can be analyzed using double-transfected cell models with the simultaneous overexpression of an uptake transport and an export pump in vectorial transport assays, thereby mimicking physiological transport processes, e.g., in liver or kidney.
EVALuna2:8709

Biomarkers for In Vivo Assessment of Transporter Function - Mueller, Fabian; Sharma, Ashish; König, Jörg; Fromm, Martin (Pharmacological Reviews, 2018)
Drug-drug interactions are a major concern not only during clinical practice, but also in drug development. Due to limitations of in vitro-in vivo predictions of transporter-mediated drug-drug interactions, multiple clinical Phase I drug-drug interaction studies may become necessary for a new molecular entity to assess potential drug interaction liabilities. This is a resource-intensive process and exposes study participants, who frequently are healthy volunteers without benefit from study treatment, to the potential risks of a new drug in development. Therefore, there is currently a major interest in new approaches for better prediction of transporter-mediated drug-drug interactions. In particular, researchers in the field attempt to identify endogenous compounds as biomarkers for transporter function, such as hexadecanedioate, tetradecanedioate, coproporphyrins I and III, or glycochenodeoxycholate sulfate for hepatic uptake via organic anion transporting polypeptide 1B or N1-methylnicotinamide for multidrug and toxin extrusion protein-mediated renal secretion. We summarize in this review the currently proposed biomarkers and potential limitations of the substances identified to date. Moreover, we suggest criteria based on current experiences, which may be used to assess the suitability of a biomarker for transporter function. Finally, further alternatives and supplemental approaches to classic drug-drug interaction studies are discussed.
EVALuna2:34655

Cancer-Type Organic Anion Transporting Polypeptide 1B3 Is Localized in Lysosomes and Mediates Resistance against Kinase Inhibitors - Haberkorn, Bastian; Oswald, Stefan; Kehl, Niklas; Geßner, Arne; Taudte, Verena; Dobert, Jan; Zunke, Friederike; Fromm, Martin; König, Jörg (Molecular Pharmacology, 2022)
Cancer-type organic anion transporting polypeptide 1B3 (CtOATP1B3), a splice variant of the hepatic uptake transporter OATP1B3 (liver-type), is expressed in several tumor entities, including colorectal carcinoma (CRC) and breast cancer. In CRC, high OATP1B3 expression has been associated with reduced progression-free and overall survival. Several kinase inhibitors used for antitumor treatment are substrates and/or inhibitors of OATP1B3 (e.g., encorafenib, vemurafenib). The functional importance of CtOATP1B3 has not been elucidated so far. Human embryonic kidney 293 cells stably overexpressing Ct-OATP1B3 protein were established and compared with control cells. Confocal laser scanning microscopy, immunoblot, and proteomics-based expression analysis demonstrated that Ct-OATP1B3 protein is intracellularly localized in lysosomes of stably transfected cells. Cytotoxicity experiments showed that cells recombinantly expressing the Ct-OATP1B3 protein were more resistant against the kinase inhibitor encorafenib compared with control cells [e.g., encorafenib (100 mM) survival rates: 89.5% versus 52.8%]. In line with these findings, colorectal cancer DLD1 cells endogenously expressing Ct-OATP1B3 protein had poorer survival rates when the OATP1B3 substrate bromosulfophthalein (BSP) was coincubated with encorafenib or vemurafenib compared with the incubation with the kinase inhibitor alone. This indicates a competitive inhibition of Ct-OATP1B3–mediated uptake into lysosomes by BSP. Accordingly, mass spectrometry-based drug analysis of lysosomes showed a reduced lysosomal accumulation of encorafenib in DLD1 cells additionally exposed to BSP. These results demonstrate that Ct-OATP1B3 protein is localized in the lysosomal membrane and can mediate transport of certain kinase inhibitors into lysosomes, revealing a new mechanism of resistance.
Created from Fastlane, Scopus look-up

Carbamazepine efficacy in a severe electro-clinical presentation of SLC13A5-epilepsy - Santalucia, Roberto; Vilain, Catheline; Soblet, Julie; De Laet, Corinne; Vuckovic, Aline; König, Jörg; Aeby, Alec (Annals of Clinical and Translational Neurology, 2022)
Recessive mutations in the SLC13A5 gene encoding the sodium-dependent citrate transporter are a recently identified cause of developmental and epileptic encephalopathy. Here, we describe a child harboring a novel homozygous loss-of-function mutation in the SLC13A5 gene (c.1496C>T–p.Ser499Phe) and exhibiting an unusual extremely severe neonatal presentation with drug-resistant seizures and burst-suppression EEG pattern. Early carbamazepine use resulted in dramatic improvement both clinically and on EEG features. Follow-up from the neonatal period to the age of 4 years is documented. This case expands the electro-clinical phenotype associated with SLC13A5-related disease and confirms the efficacy and safety of carbamazepine in nonstructural early-onset epilepsies.
CRIS-Team Scopus Importer:2022-06-03

cDNA cloning of the hepatocyte canalicular isoform of the multidrug resistance protein, cMrp, reveals a novel conjugate export pump deficient in hyperbilirubinemic mutant rats - König, Jörg; et al. (Journal of Biological Chemistry, 1996)
ATP-dependent transport of glutathione and glucuronate conjugates from hepatocytes into bile is mediated by a distinct member of the ATP-binding cassette superfamily. We have cloned and sequenced the canalicular isoform of the multidrug resistance protein from rat liver, and termed it cMrp. This membrane glycoprotein is composed of 1541 amino acids with an identity of 47.8% with the human multidrug resistance protein (MRP) and of 41.9% with the yeast cadmium factor (YCF1). The carboxyl-terminal 130 amino acids of the human hepatocyte canalicular isoform of MRP (cMRP) were 80.2% identical with rat cMrp. cMrp was not expressed in the liver of two mutant rat strains, the Eisai hyperbilirubinemic rat and the GY/TR- mutant, which are deficient in the ATP-dependent transport of conjugates across the canalicular membrane. Immunoblotting using an antibody raised against the carboxyl terminus of cMrp detected the glycoprotein of about 190 kDa only in the canalicular membrane from normal liver. Double immunofluorescence and confocal laser scanning microscopy localized cMrp exclusively to the canalicular membrane domain of hepatocytes and demonstrated its loss in the hyperbilirubinemic mutant rat. The results identify cMrp as a canalicular transport protein with a novel sequence and with a function similar to the one of the MRP.
Created from Fastlane, Scopus look-up

Cell-Specific Transport and Thyroid Hormone Receptor Isoform Selectivity Account for Hepatocyte-Targeted Thyromimetic Action of MGL-3196 - Hönes, Georg Sebastian; Sivakumar, Ramona Gowry; Hoppe, Christoph; König, Jörg; Führer, Dagmar; Moeller, Lars Christian (International Journal of Molecular Sciences, 2022)
Thyroid hormones (THs) and TH receptor-beta (TRβ) reduce hepatic triglycerides, indicating a therapeutic potential for TH analogs in liver steatosis. To avoid adverse extrahepatic, especially TRα-mediated effects such as tachycardia and bone loss, TH analogs with combined TRβ and hepatocyte specificity are desired. MGL-3196 is a new TH analog that supposedly meets these criteria. Here, we characterize the thyromimetic potential of MGL-3196 in cell-based assays and address its cellular uptake requirements. We studied the contribution of liver-specific organic anion transporters (OATP)1B1 and 1B3 to MGL-3196 action. The TR isoform-specific efficacy of MGL-3196 compared with 3,5,3′-triiodothyronine (T3) was determined with luciferase assays and gene expression analysis in OATP1B1 and OATP1B3 and TRα- or TRβ-expressing cells and in primary murine hepatocytes (PMHs) from wild-type and TRβ knockout mice. We measured the oxygen consumption rate to compare the effects of MGL-3196 and T3 on mitochondrial respiration. We identified OATP1B1 as the primary transporter for MGL-3196. MGL-3196 had a high efficacy (90% that of T3) in activating TRβ, while the activation of TRα was only 25%. The treatment of PMHs with T3 and MGL-3196 at EC50 resulted in a similar induction of Dio1 and repression of Serpina7. In HEK293 cells stably expressing OATP1B1, MGL-3196 had comparable effects on mitochondrial respiration as T3. These data indicate that MGL-3196’s hepatic thyromimetic action, the basis for its therapeutic use, results from a combination of hepatocyte-specific transport by OATP1B1 and the selective activation of TRβ over TRα.
CRIS-Team Scopus Importer:2022-12-09
Keywords: MGL-3196; OATP1B1; Resmetirom; thyroid hormone action; thyroid hormone analog; thyroid hormone transport; thyromimetic

Characterization of the human multidrug resistance protein isoform MRP3 localized to the basolateral hepatocyte membrane - König, Jörg; et al. (Hepatology, 1999)
Several members of the multidrug resistance protein (MRP) family are expressed in the liver. Adenosine triphosphate (ATP)-dependent transport of glutathione and glucuronoside conjugates across the hepatocyte canalicular membrane is mediated by the apical MRP isoform, MRP2 (APMRP), also known as canalicular multispecific organic anion transporter (cMOAT). We have cloned an additional MRP isoform, MRP3, from human liver and localized it to the basolateral membrane domain of hepatocytes. Basolateral MRP (BLMRP) is composed of 1,527 amino acids and encoded by 4,581 base pairs of complementary DNA. Northern blotting of various human tissues indicated an expression of MRP3 in the liver, colon, pancreas, and, at a lower level, in the kidney. The amino acid identity of MRP3 with MRP1 and MRP2 is 58% and 48%, respectively. These three isoforms, encoded by genes on different chromosomes, have a similar predicted topology of transmembrane segments and ATP-binding domains. Antibodies raised against two peptide sequences of MRP3 that are not shared by other MRP family members detected recombinant MRP3 expressed in polarized MDCK cells. Both antibodies served to localize MRP3 to the basolateral membrane of hepatocytes. Double-label immunofluorescence microscopy confirmed that MRP3 was not detectable in the canalicular membrane domain. A particularly strong expression of the MRP3 protein was observed in the basolateral hepatocyte membrane of two patients with Dubin-Johnson syndrome who are deficient in MRP2. These results indicate that the basolateral MRP isoform, MRP3, may be upregulated when the canalicular secretion of anionic conjugates by MRP2 is impaired.
Created from Fastlane, Scopus look-up

Clinical Aspects of Transporter-Mediated Drug–Drug Interactions - Geßner, Arne; König, Jörg; Fromm, Martin (Clinical Pharmacology & Therapeutics, 2019)
Drug transporters play an essential role in disposition and effects of multiple drugs. Plasma concentrations of the victim drug can be modified by drug–drug interactions occurring in enterocytes (e.g., P-glycoprotein), hepatocytes (e.g., organic anion-transporting polypeptide 1B1 (OATP1B1)), and/or renal proximal tubular cells (e.g., organic cation transporter 2 (OCT2)/multidrug and toxin extrusion 1 and 2-K (MATE1/MATE2-K)). In addition, transporter-mediated drug–drug interactions can cause altered local tissue concentrations and possibly altered effects/toxicity (e.g., in liver and kidneys). During drug development, there is now an intensive in vitro screening of new molecular entities as transporter substrates and inhibitors, followed if necessary by drug–drug interaction studies in healthy volunteers. Nevertheless, there are still unresolved issues, which will also be discussed in this review article (e.g., the clinical significance of transporter-mediated drug–drug interactions of particular relevance to the elderly who are prescribed multiple drugs, with additional impaired liver or kidney function, and the extent to which medication safety in real life could be improved by a reduction of those interactions).
CRIS-Team Scopus Importer:2019-05-21

Contribution of MATE1 to Renal Secretion of the NMDA Receptor Antagonist Memantine - Mueller, Fabian; Weitz, Dietmar; Derdau, Volker; Sandvoss, Martin; Mertsch, Katharina; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2017)
The weak base memantine is actively secreted into urine, however the underlying mechanisms are insufficiently understood. Potential candidates involved in memantine renal secretion are organic cation transporter 2 (OCT2) and multidrug and toxin extrusion proteins (MATE1, MATE2-K). The aim of this in vitro study was the examination of the interaction of memantine with OCT2 and MATEs. Memantine transporter inhibition and transport were examined in HEK cells expressing human OCT2, MATE1, or MATE2-K. Monolayers of single- (MDCK-OCT2, MDCK-MATE1) and double-transfected MDCK cells (MDCK-OCT2-MATE1) were used for studies on vectorial, basal to apical memantine transport. Memantine inhibited OCT2-, MATE1-, and MATE2-K-mediated metformin transport with IC50 values of 3.2, 40.9, and 315.3 μM, respectively. In HEK cells, no relevant memantine uptake by OCT2, MATE1, or MATE2-K was detected. Vectorial transport experiments, however, indicated a role of MATE1 for memantine export: After memantine administration to the basal side of the monolayers, memantine cellular accumulation was considerably lower (MDCK-MATE1 vs MDCK control cells, P < 0.01) and memantine transcellular, basal to apical transport was higher in MATE1 expressing cells (MDCK-MATE1 vs MDCK control cells, P < 0.001 at 60 and 180 min). Both effects were abolished upon addition of the MATE inhibitor cimetidine. These experiments suggest a relevant role of MATE1 for renal secretion of memantine. In the clinical setting, renal elimination of memantine could be impaired by coadministration of MATE inhibitors.
EVALuna2:34656

Contribution of multidrug and toxin extrusion protein 1 (MATE1) to renal secretion of trimethylamine-N-oxide (TMAO) - Geßner, Arne; König, Jörg; Fromm, Martin (Scientific Reports, 2018)
Trimethylamine-N-oxide (TMAO) gained considerable attention because of its role as a cardiovascular risk biomarker. Organic cation transporter 2 (OCT2) mediates TMAO uptake into renal proximal tubular cells. Here we investigated the potential role of multidrug and toxin extrusion protein 1 (MATE1) for translocation of TMAO across the luminal membrane of proximal tubular cells. HEK293 cells stably expressing OCT2 (HEK-OCT2) or MATE1 (HEK-MATE1) were used for uptake studies. Transcellular transport of TMAO was investigated using monolayers of MDCK control cells (MDCK-Co) as well as single- (MDCK-OCT2, MDCK-MATE1) and double-transfected cells (MDCK-OCT2-MATE1). In line with previous studies, HEK-OCT2 cells revealed a 2.4-fold uptake of TMAO compared to control cells (p < 0.001), whereas no significant uptake was observed in HEK-MATE1. In monolayers of MDCK cells, polarised TMAO transcellular transport was not significantly different between MDCK-Co and MDCK-OCT2 cells, but significantly increased in MDCK-MATE1 (p < 0.05) and MDCK-OCT2-MATE1 cells (p < 0.001). The OCT/MATE inhibitor trimethoprim abolished TMAO translocation in MDCK-OCT2-MATE1 cells (p < 0.05). The present data suggest that MATE1 contributes to renal elimination of TMAO. For selected MATE substrates, such as TMAO, uptake studies using non-polarised MATE-expressing cells can reveal false negative results compared to studies using polarised monolayers.
EVALuna2:34654

Deletion of the diabetes candidate gene Slc16a13 in mice attenuates diet-induced ectopic lipid accumulation and insulin resistance - Schumann, Tina; König, Jörg; von Loeffelholz, Christian; Vatner, Daniel F.; Zhang, Dongyan; Perry, Rachel J.; Bernier, Michel; Chami, Jason; Henke, Christine; Kurzbach, Anica; El-Agroudy, Nermeen N.; Willmes, Diana M.; et al. (Communications Biology, 2021)
Genome-wide association studies have identified SLC16A13 as a novel susceptibility gene for type 2 diabetes. The SLC16A13 gene encodes SLC16A13/MCT13, a member of the solute carrier 16 family of monocarboxylate transporters. Despite its potential importance to diabetes development, the physiological function of SLC16A13 is unknown. Here, we validate Slc16a13 as a lactate transporter expressed at the plasma membrane and report on the effect of Slc16a13 deletion in a mouse model. We show that Slc16a13 increases mitochondrial respiration in the liver, leading to reduced hepatic lipid accumulation and increased hepatic insulin sensitivity in high-fat diet fed Slc16a13 knockout mice. We propose a mechanism for improved hepatic insulin sensitivity in the context of Slc16a13 deficiency in which reduced intrahepatocellular lactate availability drives increased AMPK activation and increased mitochondrial respiration, while reducing hepatic lipid content. Slc16a13 deficiency thereby attenuates hepatic diacylglycerol-PKCε mediated insulin resistance in obese mice. Together, these data suggest that SLC16A13 is a potential target for the treatment of type 2 diabetes and non-alcoholic fatty liver disease.
CRIS-Team Scopus Importer:2021-07-16

Differential uptake of arginine derivatives by the human heteromeric amino acid transporter b0,+AT-rBAT (SLC7A9-SLC3A1) - Banjarnahor, Sofna; Scherpinski, Lorenz; Keller, Max; König, Jörg; Maas, Renke (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
L-arginine and its (patho-)physiologically active derivatives, L-homoarginine and asymmetric dimethylarginine (ADMA), show significant differences in their renal clearance. The underlying molecular mechanisms remain to be elucidated, but selective tubular transport protein-mediated mechanisms likely play a role. In the present study, we investigate the human heteromeric transporter b0,+AT-rBAT (encoded by the SLC7A9 and SLC3A1 genes) as a potential candidate because it is localized in the luminal membrane of human proximal tubule cells and capable of mediating the cellular uptake of amino acids, including L-arginine. Double-transfected Madin-Darby canine kidney (MDCK) cells stably expressing human b0,+AT-rBAT exhibited significant uptake of L-arginine and L-homoarginine, with apparent Km values of 512.6 and 197.0 μM, respectively. On the contrary, ADMA uptake was not saturated up to 4000 μM, with a transport rate > 5 nmol × mg protein−1 × min−1. With an IC50 value of 115.8 μM, L-arginine inhibited L-homoarginine uptake. Conversely, L-arginine only exhibited a partial inhibitory effect on ADMA uptake. Taken together, our data indicate that b0,+AT-rBAT may contribute to the differential renal handling of L-arginine, L-homoarginine, and ADMA.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ADMA; b; L-arginine; L-homoarginine; Proximal tubule; SLC3A1; SLC7A9; Transport

Drug Resistance and ATP-dependent Conjugate Transport Mediated by the Apical Multidrug Resistance Protein, MRP2, Permanently Expressed in Human and Canine Cells - König, Jörg; Cui, Yunhai; Buchholz, Ulrike; Spring, Herbert; Leier, Inka; Keppler, Dietrich (Molecular Pharmacology, 1999)

Esters of Bendamustine Are by Far More Potent Cytotoxic Agents than the Parent Compound against Human Sarcoma and Carcinoma Cells - Huber, Stefan; Huettner, Johannes Philip; Hacker, Kristina; Bernhardt, Guenther; König, Jörg; Buschauer, Armin (PLoS ONE, 2015)
The alkylating agent bendamustine is approved for the treatment of hematopoietic malignancies such as non-Hodgkin lymphoma, chronic lymphocytic leukemia and multiple myeloma. As preliminary data on recently disclosed bendamustine esters suggested increased cytotoxicity, we investigated representative derivatives in more detail. Especially basic esters, which are positively charged under physiological conditions, were in the crystal violet and the MTT assay up to approximately 100 times more effective than bendamustine, paralleled by a higher fraction of early apoptotic cancer cells and increased expression of p53. Analytical studies performed with bendamustine and representative esters revealed pronounced cellular accumulation of the derivatives compared to the parent compound. In particular, the pyrrolidinoethyl ester showed a high enrichment in tumor cells and inhibition of OCT1- and OCT3-mediated transport processes, suggesting organic cation transporters to be involved. However, this hypothesis was not supported by the differential expression of OCT1 (SLC22A1) and OCT3 (SLC22A3), comparing a panel of human cancer cells. Bendamustine esters proved to be considerably more potent cytotoxic agents than the parent compound against a broad panel of human cancer cell types, including hematologic and solid malignancies (e.g. malignant melanoma, colorectal carcinoma and lung cancer), which are resistant to bendamustine. Interestingly, spontaneously immortalized human keratinocytes, as a model of "normal" cells, were by far less sensitive than tumor cells against the most potent bendamustine esters.
EVALuna2:8695

Exon-intron organization of the human multidrug-resistance protein 2 (MRP2) gene mutated in Dubin-Johnson syndrome - König, Jörg; et al. (Gastroenterology, 1999)
Background and Aims: The Dubin-Johnson syndrome is characterized by conjugated hyperbilirubinemia and by impaired secretion of anionic conjugates from hepatocytes into bile. Absence of the multidrug-resistance protein 2 (MRP2; symbol ABCC2), an adenosine triphosphate-dependent conjugate export pump, from the hepatocyte canalicular membrane is the molecular basis of this syndrome. The aim of this study was the elucidation of all exon-intron boundaries of the MRP2 gene as a prerequisite for the analysis of mutations in patients with Dubin-Johnson syndrome. Methods: Exon-intron boundaries of MRP2 were determined, and the amplified exons were screened for mutations. Immunofluorescence microscopy served to localize the MRP2 protein in human liver. Results: The human MRP2 gene is 45 kilobases long; it contains 32 exons and a high proportion of class 0 introns. In 2 patients with Dubin- Johnson syndrome, we detected a nonsense mutation at codon 1066 and a 6- nucleotide deletion mutation affecting codons 1392-1394. The MRP2 protein was absent from the canalicular membrane of both patients. Conclusions: The mutations detected so far show that various mutations in the MRP2 gene can lead to the Dubin-Johnson syndrome. The exon-intron boundaries established in this article will facilitate the analysis of additional mutations in the MRP2 gene.
Created from Fastlane, Scopus look-up

Exploring Structural Determinants of Bias among D4 Subtype-Selective Dopamine Receptor Agonists - Graßl, Fabian; Bock, Leonard; Huete-Huerta González, Álvaro; Schiller, Martin; Gmeiner, Peter; König, Jörg; Fromm, Martin; Hübner, Harald; Heinrich, Markus (Journal of Medicinal Chemistry, 2023)
The high affinity dopamine D4 receptor ligand APH199 and derivatives thereof exhibit bias toward the Gi signaling pathway over β-arrestin recruitment compared to quinpirole. Based on APH199, two novel groups of D4 subtype selective ligands were designed and evaluated, in which the original benzyl phenylsemicarbazide substructure was replaced by either a biphenylmethyl urea or a biphenyl urea moiety. Functional assays revealed a range of different bias profiles among the newly synthesized compounds, namely, with regard to efficacy, potency, and GRK2 dependency, in which bias factors range from 1 to over 300 and activation from 15% to over 98% compared to quinpirole. These observations demonstrate that within bias, an even more precise tuning toward a particular profile is possible, which─in a general sense─could become an important aspect in future drug development. Docking studies enabled further insight into the role of the ECL2 and the EPB in the emergence of bias, thereby taking advantage of the diversity of functionally selective D4 agonists now available.
CRIS-Team Scopus Importer:2023-08-11

Exposure of Fexofenadine, but Not Pseudoephedrine, Is Markedly Decreased by Green Tea Extract in Healthy Volunteers - Misaka, Shingen; Ono, Yuko; Taudte, Verena; Hoier, Eva; Ogata, Hiroshi; Ono, Tomoyuki; König, Jörg; Watanabe, Hiroshi; Fromm, Martin; Shimomura, Kenju (Clinical Pharmacology & Therapeutics, 2022)
Green tea (GT) alters the disposition of a number of drugs, such as nadolol and lisinopril. However, it is unknown whether GT affects disposition of hydrophilic anti-allergic drugs. The purpose of this study was to investigate whether pharmacokinetics of fexofenadine and pseudoephedrine are affected by catechins, major GT components. A randomized, open, 2-phase crossover study was conducted in 10 healthy Japanese volunteers. After overnight fasting, subjects were simultaneously administered fexofenadine (60 mg) and pseudoephedrine (120 mg) with an aqueous solution of green tea extract (GTE) containing (−)-epigallocatechin gallate (EGCG) of 300 mg or water (control). In vitro transport assays were performed using HEK293 cells stably expressing organic anion transporting polypeptide (OATP)1A2 to evaluate the inhibitory effect of EGCG on OATP1A2-mediated fexofenadine transport. In the GTE phase, the area under the plasma concentration-time curve and the amount excreted unchanged into urine for 24 hours of fexofenadine were significantly decreased by 70% (P < 0.001) and 67% (P < 0.001), respectively, compared with control. There were no differences in time to maximum plasma concentration and the elimination half-life of fexofenadine between phases. Fexofenadine was confirmed to be a substrate of OATP1A2, and EGCG (100 and 1,000 μM) and GTE (0.1 and 1 mg/mL) inhibited OATP1A2-mediated uptake of fexofenadine. On the contrary, the concomitant administration of GTE did not influence the pharmacokinetics of pseudoephedrine. These results suggest that intake of GT may result in a markedly reduced exposure of fexofenadine, but not of pseudoephedrine, putatively by inhibiting OATP1A2-mediated intestinal absorption.
CRIS-Team Scopus Importer:2022-07-08

Expression and localization of the multidrug resistance proteins MRP2 and MRP3 in human gallbladder epithelia - König, Jörg; et al. (Gastroenterology, 2001)
Background & Aims: The multidrug resistance protein (MRP) isoforms MRP2 (ABCC2) and MRP3 (ABCC3) play a decisive role in the hepatic secretion of endogenous and xenobiotic conjugates and are differentially expressed in hepatocytes and cholangiocytes. The epithelium of the gallbladder considerably modifies the composition of primary hepatic bile by absorption and secretion; however, the underlying transport mechanisms were largely unknown. Localization of MRP2 and MRP3 may provide an explanation of how the products of phase II conjugation are effluxed from gallbladder epithelia. Methods: Expression and localization of MRP2 and MRP3 were analyzed by reverse-transcription polymerase chain reaction (RT-PCR) and immunofluorescence microscopy of human gallbladder tissue. Results: Expression of MRP2 and MRP3 was identified in all gallbladders by RT-PCR followed by sequencing of the amplified fragments. Double immunofluorescence microscopy using 2 specific antibodies for the respective MRP isoform showed the simultaneous expression of MRP2 in the apical membrane and MRP3 in the basolateral membrane of gallbladder epithelia. MRP1 protein expression was not detectable. Conclusions: Our findings show the expression of MRP2 and MRP3 in distinct plasma membrane domains of gallbladder epithelia and provide evidence for the capacity of the gallbladder to secrete xenobiotic and endogenous anionic conjugates into blood via MRP3 and into bile via MRP2.
Created from Fastlane, Scopus look-up

Expression, localization and functional analysis of cancer type OATP1B3 in different stably transfected cell lines - Haberkorn, Bastian; König, Jörg; Fromm, Martin (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2019)
CRIS-Team WoS Importer:2019-02-21

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine - Lueneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M.; Xanthakis, Vanessa; Glazer, Nicole L.; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T.; et al. (Circulation-Cardiovascular Genetics, 2014)
Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers.This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium.These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
EVALuna2:8688

Heteroaryl derivatives of suvorexant as OX1R selective PET ligand candidates: Cu-mediated 18F-fluorination of boroxines, in vitro and initial in vivo evaluation - Bolik, Kim-Viktoria; Hellmann, Jan; Maschauer, Simone; Neu, Eduard; Einsiedel, Jürgen; Riss, Patrick; Vogg, Nora; König, Jörg; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (EJNMMI Research, 2024)
Background: The orexin receptor (OXR) plays a role in drug addiction and is aberrantly expressed in colorectal tumors. Subtype-selective OXR PET ligands suitable for in vivo use have not yet been reported. This work reports the development of 18F-labeled OXR PET ligand candidates derived from the OXR antagonist suvorexant and the OX1R-selective antagonist JH112. Results: Computational analysis predicted that fluorine substitution (1e) and introduction of the fluorobenzothiazole scaffold (1f) would be suitable for maintaining high OX1R affinity. After multi-step synthesis of 1a–1f, in vitro OXR binding studies confirmed the molecular dynamics calculations and revealed single-digit nanomolar OX1R affinities for 1a–f, ranging from 0.69 to 2.5 nM. The benzothiazole 1f showed high OX1R affinity (Ki = 0.69 nM), along with 77-fold subtype selectivity over OX2R. Cu-mediated 18F-fluorination of boroxine precursors allowed for a shortened reaction time of 5 min to provide the non-selective OXR ligand [18F]1c and its selective OX1R congener [18F]1f in activity yields of 14% and 22%, respectively, within a total synthesis time of 52–76 min. [18F]1c and [18F]1f were stable in plasma and serum in vitro, with logD7.4 of 2.28 ([18F]1c) and 2.37 ([18F]1f), and high plasma protein binding of 66% and 77%, respectively. Dynamic PET imaging in rats showed similar brain uptake of [18F]1c (0.17%ID/g) and [18F]1f (0.15%ID/g). However, preinjection of suvorexant did not significantly block [18F]1c or [18F]1f uptake in the rat brain. Pretreatment with cyclosporine A to study the role of P-glycoprotein (P-gp) in limiting brain accumulation moderately increased brain uptake of [18F]1c and [18F]1f. Accordingly, in vitro experiments demonstrated that the P-gp inhibitor zosuquidar only moderately inhibited polarized, basal to apical transport of 1c (p < 0.05) and had no effect on the transport of 1f, indicating that P-gp does not play a relevant role in brain accumulation of [18F]1c and [18F]1f in vivo. Conclusions: The in vitro and in vivo results of [18F]1c and [18F]1f provide a solid basis for further development of suitable OXR PET ligands for brain imaging.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Cu-mediated; F-18; Orexin receptor; PET; Suvorexant

Human Mast Cells Secreting Leukotriene C4Express the MRP1 Gene-Encoded Conjugate Export Pump - König, Jörg; et al. (Biological Chemistry, 1998)
Mast cells are known to secrete endogenously synthesized leukotriene C4(LTC4), but the identity of the responsible export pump in human mast cells was unknown. The multidrug resistance proteins MRP1 and MRP2 have been identified as primary-active ATP-dependent export pumps for various amphiphilic anions including the glutathione conjugate LTC4. We therefore studied the expression at the RNA and protein levels of both MRP1 and MRP2 as well as the ATP-dependent LTC4transport in the human mast cell line HMC-1. Upon stimulation by 1 µM ionomycin, intact HMC-1 cells generated 26pmol LTC4108cells within 20 min. Transport experiments using inside-out HMC-1 membrane vesicles demonstrated an ATP-dependent LTC4transport amounting to 1.4pmol × (mg protein)-1× min-1. Reverse transcription PCR indicated that HMC-1 cells express mRNA of MRP1, but not of MRP2 or MRP3. Cloning and sequencing of the amplified PCR fragment confirmed its identity with the human MRP1 sequence. Immunoblots using antibodies against MRP1 and MRP2 demonstrated that HMC-1 cells contain the MRP1 but not the MRP2 protein. Our results indicate that the 190 kDa integral membrane glycoprotein MRP1 mediates the ATP-dependent export of LTC4from human mast cells to the extracellular space. © 1998, Walter de Gruyter. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: ABC-Transporter; Conjugate export pump; Cysteinyl leukotrienes; Mast cells; Multidrug resistance protein

Human multidrug resistance protein 8 (MRP8/ABCC11), an apical efflux pump for steroid sulfates, is an axonal protein of the CNS and peripheral nervous system - König, Jörg; et al. (Neuroscience, 2006)
Dehydroepiandrosterone 3-sulfate and other neurosteroids are synthesized in the CNS and peripheral nervous system where they may modulate neuronal excitability by interacting with ligand-gated ion channels. For this modulatory activity, neurosteroids have to be locally released from either neurons or glial cells. We here identify the integral membrane protein ABCC11 (multidrug resistance protein 8) as an ATP-dependent efflux pump for steroid sulfates, including dehydroepiandrosterone 3-sulfate, and localize it to axons of the human CNS and peripheral nervous system. ABCC11 mRNA was detected in human brain by real-time polymerase chain reaction. Antibodies raised against ABCC11 served to detect the protein in brain by immunoblotting and immunofluorescence microscopy. ABCC11 was preferentially found in the white matter of the brain and co-localized with neurofilaments indicating that it is an axonal protein. Additionally, ABCC11 was localized to axons of the peripheral nervous system. For functional studies, ABCC11 was expressed in polarized Madin-Darby canine kidney cells where it was sorted to the apical membrane. This apical sorting is in accordance with the localization of ABCC11 to the axonal membrane of neurons. Inside-out plasma membrane vesicles containing recombinant ABCC11 mediated ATP-dependent transport of dehydroepiandrosterone 3-sulfate with a Km value of 21 μM. This transport function together with the localization of the ABCC11 protein in vicinity to GABAA receptors is consistent with a role of ABCC11 in dehydroepiandrosterone 3-sulfate release from neurons to sites of dehydroepiandrosterone 3-sulfate-mediated receptor modulation. Our findings may provide a basis for the characterization of mutations in the human ABCC11 gene and their linkage with neurological disorders. © 2005 Published by Elsevier Ltd on behalf of IBRO.
Created from Fastlane, Scopus look-up
Keywords: Dehydroepiandrosterone 3-sulfate; GABA; Gliomas; Multidrug resistance proteins; Neurosteroids; Paroxysmal kinesigenic choreoathetosis

Importance of OCT2 and MATE1 for the Cimetidine-Metformin Interaction: Insights from Investigations of Polarized Transport in Single- And Double-Transfected MDCK Cells with a Focus on Perpetrator Disposition - Mueller, Fabian; Weitz, Dietmar; Mertsch, Katharina; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2018)
Cimetidine decreases the renal clearance of metformin by inhibition of renal tubular cation transport, and the underlying molecular mechanisms are still not fully understood. We investigated polarized metformin transport without and with the addition of cimetidine as well as polarized cimetidine transport in double-transfected MDCK-OCT2-MATE1 cells that mimic organic cation transport processes in proximal renal tubule cells and in MDCK vector control and single-transfected MDCK-OCT2 and MDCK-MATE1 cells. At all tested concentrations (1, 10, 100 μM), the intracellular accumulation of cimetidine after administration to the basal compartment was considerably higher in MDCK-OCT2 cells compared to that in all other cells ( p < 0.001). Whereas cimetidine transcellular, basal-to-apical transport was only slightly higher in MDCK-OCT2 cells, the presence of MATE1 in the apical membrane caused a pronounced translocation of cimetidine in both single- and double-transfected cells ( p < 0.001). Transcellular, basal-to-apical metformin net transport was reduced by 89.1, 74.5, and 91.0% in MDCK-OCT2-MATE1 cells after the addition of cimetidine (100 μM) to the basal, the apical, or both compartments ( p < 0.001). In MDCK-MATE1 and MDCK-OCT2-MATE1 cells, transcellular net transport of metformin was inhibited by cimetidine with IC50 values of 8.0 and 6.6 μM, respectively. Our data confirm the relevance of MATE1 and suggest the relevance of OCT2 for the cimetidine-metformin interaction, primarily because OCT2 mediates uptake of the perpetrator cimetidine into renal proximal tubular cells and thereby to the site of the metformin exporter MATE1. This work supports the notion that a thorough understanding of transporter-mediated drug-drug interactions may require investigations on the impact of transporters on cellular uptake and transcellular transport of victim as well as perpetrator drugs.
EVALuna2:34651

Inhibition of Mouse Erythroid Band 3-Mediated Chloride Transport by Site-Directed Mutagenesis of Histidine Residues and Its Reversal by Second Site Mutation of Lys 558, the Locus of Covalent H2DIDS Binding - König, Jörg; et al. (Biochemistry, 1995)
Substitution by site-directed mutagenesis of any one of the histidine residues H721, H837, and H852 by glutamine, or of H752 by serine, inhibits Cl” flux mediated by band 3 expressed in Xenopus oocytes. Mutation of Lys 558 (K558N), the site of covalent binding of H2DIDS (4,4'-diisothiocyanostilbene- 2,2'-disulfonate) in the outer membrane surface, in combination with any one of the His/Gln mutations leads to partial (H721Q; H837Q) or complete (H852Q) restoration of Cl- flux. In contrast, inhibition of Cl- flux by mutation of proline or lysine residues in the vicinity of His 837 at the inner membrane surface cannot be reversed by the second-site mutation K558N, indicating specificity of interaction between Lys 558 and His 837. The histidine-specific reagent diethyl pyrocarbonate (DEPC) is known to inhibit band 3-mediated anion exchange in red blood cells [Izuhara, K., Okubo, K., & Hamasaki, N. (1989) Biochemistry 28, 4725-4728], It was also found to inhibit transport after expression in the oocyte of wild-type band 3, of the double mutants of the histidines listed above, and of the single mutant H752S. The effects on the wild type and the double mutants were indistinguishable, while the mutant H752S exhibited a considerably reduced sensitivity to inhibition, suggesting that His 752 is the most prominent site of action of DEPC. According to a hydrophobicity plot of band 3 and further independent evidence, Lys 558, the mutated histidines, and Glu 699, the mutation of which was also found to inhibit Cl- flux [Miiller-Berger, S., Karbach, D., Kang, D., Aranibar, N., Wood, P. G., RÖterjans, H., & Passow, H. (1995) Biochemistry 34, 9325-9332], are most likely located in five different transmembrane helices. The interactions between Lys 558 and the various histidines suggest that these helices reside in close proximity. Together with the helix carrying Glu 699, they could form an access channel lined with an array of alternating histidine and glutamate residues. Together with a chloride ion bridging the gap between His 852 and His 837, they could have the potential to form, at low pH, a transmembrane chain of hydrogen bonds. The possible functional significance of such channel is discussed. © 1995, American Chemical Society. All rights reserved.
Created from Fastlane, Scopus look-up

Inhibitory Effects of Green Tea and (-)-Epigallocatechin Gallate on Transport by OATP1B1, OATP1B3, OCT1, OCT2, MATE1, MATE2-K and P-Glycoprotein - Knop, Jana; Misaka, Shingen; Singer, Katrin; Hoier, Eva; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (PLoS ONE, 2015)
Green tea catechins inhibit the function of organic anion transporting polypeptides (OATPs) that mediate the uptake of a diverse group of drugs and endogenous compounds into cells. The present study was aimed at investigating the effect of green tea and its most abundant catechin epigallocatechin gallate (EGCG) on the transport activity of several drug transporters expressed in enterocytes, hepatocytes and renal proximal tubular cells such as OATPs, organic cation transporters (OCTs), multidrug and toxin extrusion proteins (MATEs), and P-glycoprotein (P-gp). Uptake of the typical substrates metformin for OCTs and MATEs and bromosulphophthalein (BSP) and atorvastatin for OATPs was measured in the absence and presence of a commercially available green tea and EGCG. Transcellular transport of digoxin, a typical substrate of P-gp, was measured over 4 hours in the absence and presence of green tea or EGCG in Caco-2 cell monolayers. OCT1-, OCT2-, MATE1- and MATE2-K-mediated metformin uptake was significantly reduced in the presence of green tea and EGCG (P < 0.05). BSP net uptake by OATP1B1 and OATP1B3 was inhibited by green tea [IC50 2.6% (v/v) and 0.39% (v/v), respectively]. Green tea also inhibited OATP1B1- and OATP1B3-mediated atorvastatin net uptake with IC50 values of 1.9% (v/v) and 1.0% (v/v), respectively. Basolateral to apical transport of digoxin was significantly decreased in the presence of green tea and EGCG. These findings indicate that green tea and EGCG inhibit multiple drug transporters in vitro. Further studies are necessary to investigate the effects of green tea on prototoypical substrates of these transporters in humans, in particular on substrates of hepatic uptake transporters (e.g. statins) as well as on P-glycoprotein substrates.
EVALuna2:8693

Interaction of oral antidiabetic drugs with hepatic uptake transporters: focus on organic anion transporting polypeptides and organic cation transporter 1. - Bachmakov, Iouri; Gläser, Hartmut; Fromm, Martin; König, Jörg (Diabetes, 2008)
The uptake of drugs into hepatocytes is a key determinant for hepatic metabolism, intrahepatic action, their subsequent systemic plasma concentrations, and extrahepatic actions. In vitro and in vivo studies indicate that many drugs used for treatment of cardiovascular diseases (e.g., oral antidiabetic drugs, statins) are taken up into hepatocytes by distinct organic anion transporters (organic anion transporting polypeptides [OATPs]; gene symbol SLCO/SLC21) or organic cation transporters (OCTs; gene symbol SLC22). Because most patients with type 2 diabetes receive more than one drug and inhibition of drug transporters has been recognized as a new mechanism underlying drug-drug interactions, we tested the hypothesis of whether oral antidiabetic drugs can inhibit the transport mediated by hepatic uptake transporters. Using stably transfected cell systems recombinantly expressing the uptake transporters OATP1B1, OATP1B3, OATP2B1, or OCT1, we analyzed whether the antidiabetic drugs repaglinide, rosiglitazone, or metformin influence the transport of substrates and drugs (for OATPs, sulfobromophthalein [BSP] and pravastatin; for OCT1, 1-methyl-4-phenylpyridinium [MPP(+)] and metformin). Metformin did not inhibit the uptake of OATP and OCT1 substrates. However, OATP-mediated BSP and pravastatin uptake and OCT1-mediated MPP(+) and metformin uptake were significantly inhibited by repaglinide (half-maximal inhibitory concentration [IC(50)] 1.6-5.6 micromol/l) and rosiglitazone (IC(50) 5.2-30.4 micromol/l). These in vitro results demonstrate that alterations of uptake transporter function by oral antidiabetic drugs have to be considered as potential mechanisms underlying drug-drug interactions. OBJECTIVE RESEARCH DESIGN AND METHODS RESULTS CONCLUSIONS

Interaction of remdesivir with clinically relevant hepatic drug uptake transporters - Nies, Anne T.; König, Jörg; Hofmann, Ute; Kölz, Charlotte; Fromm, Martin; Schwab, Matthias (Pharmaceutics, 2021)
Remdesivir has been approved for treatment of COVID-19 and shortens the time to recovery in hospitalized patients. Drug transporters removing remdesivir from the circulation may reduce efficacy of treatment by lowering its plasma levels. Information on the interaction of remdesivir with drug transporters is limited. We therefore assessed remdesivir as substrate and inhibitor of the clinically relevant hepatic drug uptake transporters organic anion transporting poly-peptide (OATP)-1B1 (SLCO1B1), its common genetic variants OATP1B1*1b, OATP1B1*5, OATP1B1*15, as well as OATP1B3 (SLCO1B3), OATP2B1 (SLCO2B1) and organic cation transporter (OCT)-1 (SLC22A1). Previously established transporter-overexpressing cells were used to measure (i) cellular remdesivir uptake and (ii) cellular uptake of transporter probe substrates in the presence of remdesivir. There was a high remdesivir uptake into vector-transfected control cells. Moderate, but statistically significant higher uptake was detected only for OATP1B1-, OATP1B1*1b and OATP1B1*15-expressing cells when compared with control cells at 5 µM. Remdesivir inhibited all investigated transporters at 10 µM and above. In conclusion, the low uptake rates suggest that OATP1B1 and its genetic variants, OATP1B3, OATP2B1 and OCT1 are not relevant for hepatocellular uptake of remdesivir in humans. Due to the rapid clearance of remdesivir, no clinically relevant transporter-mediated drug-drug interactions are expected.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Drug transporters; Drug-drug interaction; Inhibition; OATP1B1; OATP1B3; OATP2B1; OCT1; Remdesivir

Interplay of the Organic Cation Transporters OCT1 and OCT2 with the Apically Localized Export Protein MATE1 for the Polarized Transport of Trospium - Deutsch, Birgit; Neumeister, Claudia; Schwantes, Ulrich; Fromm, Martin; König, Jörg (Molecular Pharmaceutics, 2019)
The anticholinergic drug trospium is secreted into urine and, to a smaller extent, into bile. Chemically, it is an organic cation, and it is a substrate of the uptake transporters OCT1 and OCT2 as well as for the export proteins MATE1 and MATE2-K as determined in uptake studies using HEK293 cells. So far, neither MATE-mediated export nor the interplay of OCT-mediated uptake and MATE-mediated export have been investigated. Therefore, we used polarized monolayers of single and double-transfected MDCKII cells (MDCK-OCT1, MDCK-OCT2, MDCK-MATE1, MDCK-OCTI-MATE1, and MDCK-OCT2-MATE1) and the respective control cells (MDCK-Co) for transcellular transport assays. We demonstrate that the trans cellular, basal-to-apical transport of trospium is significantly higher in all cell lines compared to control cells over nearly the complete concentration range tested. The transcellular transport mediated by double-transfected MDCK-OCTI-MATE1 and MDCK-OCT2-MATE1 exceeded that in the single-transfected cells (MDCK-OCTI-MATE1 vs MDCK-OCT1: 2.2-fold; MDCK-OCT1-MATE1 vs MDCK-MATE1: 1.7-fold; MDCK-OCT2-MATE1 vs MDCK-OCT2: 6.1-fold; MDCK-OCT2-MATE1 vs MDCK-MATE1: 1.8-fold at a trospium concentration of 1.0 mu M; p < 0.001 each). Thus, we show that MATE1 does not only mediate the uptake of trospium into HEK293 cells but also the efflux of trospium out of polarized MDCKII-cells. Furthermore, our results indicate that OCT1 or OCT2 as uptake transporters and MATE1 as an export protein contribute to the transcellular transport of trospium at concentrations normally reached during trospium therapy. These data suggest that both, OCT-mediated uptake as well as MATE1-mediated efflux may contribute to trospium renal and biliary elimination.
CRIS-Team WoS Importer:2019-02-21

L-Arginine and Cardioactive Arginine Derivatives as Substrates and Inhibitors of Human and Mouse NaCT/Nact - Surrer, Daniela; Fromm, Martin; Maas, Renke; König, Jörg (Metabolites, 2022)
The uptake transporter NaCT (gene symbol SLC13A5) is expressed in liver and brain and important for energy metabolism and brain development. Substrates include tricarboxylic acid cycle intermediates, e.g., citrate and succinate. To gain insights into the substrate spectrum of NaCT, we tested whether arginine and the cardioactive L-arginine metabolites asymmetric dimethylarginine (ADMA) and L-homoarginine are also transported by human and mouse NaCT/Nact. Using HEK293 cells overexpressing human or mouse NaCT/Nact we characterized these substances as substrates. Furthermore, inhibition studies were performed using the arginine derivative symmetric dimethylarginine (SDMA), the NaCT transport inhibitor BI01383298, and the prototypic substrate citrate. Arginine and the derivatives ADMA and L-homoarginine were identified as substrates of human and mouse NaCT. Transport of arginine and derivatives mediated by human and mouse NaCT were dose-dependently inhibited by SDMA. Whereas BI01383298 inhibited only human NaCT-mediated citrate uptake, it inhibits the uptake of arginine and derivatives mediated by both human NaCT and mouse Nact. In contrast, the prototypic substrate citrate inhibited the transport of arginine and derivatives mediated only by human NaCT. These results demonstrate a so far unknown link between NaCT/Nact and L-arginine and its cardiovascular important derivatives.
CRIS-Team Scopus Importer:2022-04-15
Keywords: arginine derivatives; cardioactive arginine metabolites; L-arginine; transport inhibition; uptake

MATE1 Deficiency Exacerbates Dofetilide-Induced Proarrhythmia - Uddin, Muhammad Erfan; Eisenmann, Eric D.; Li, Yang; Huang, Kevin M.; Garrison, Dominique A.; Talebi, Zahra; Gibson, Alice A.; Jin, Yan; Nepal, Mahesh; Bonilla, Ingrid M.; Fu, Qiang; Sun, Xinxin; et al. (International Journal of Molecular Sciences, 2022)
Dofetilide is a rapid delayed rectifier potassium current inhibitor widely used to prevent the recurrence of atrial fibrillation and flutter. The clinical use of this drug is associated with increases in QTc interval, which predispose patients to ventricular cardiac arrhythmias. The mechanisms involved in the disposition of dofetilide, including its movement in and out of cardiomyocytes, remain unknown. Using a xenobiotic transporter screen, we identified MATE1 (SLC47A1) as a transporter of dofetilide and found that genetic knockout or pharmacological inhibition of MATE1 in mice was associated with enhanced retention of dofetilide in cardiomyocytes and increased QTc prolongation. The urinary excretion of dofetilide was also dependent on the MATE1 genotype, and we found that this transport mechanism provides a mechanistic basis for previously recorded drug-drug interactions of dofetilide with various contraindicated drugs, including bictegravir, cimetidine, ketoconazole, and verapamil. The translational significance of these observations was examined with a physiologically-based pharmacokinetic model that adequately predicted the drug-drug interaction liabilities in humans. These findings support the thesis that MATE1 serves a conserved cardioprotective role by restricting excessive cellular accumulation and warrant caution against the concurrent administration of potent MATE1 inhibitors and cardiotoxic substrates with a narrow therapeutic window.
CRIS-Team WoS Importer:2022-08-26

Molecular analysis of regulation of gene expression of the human erythroid anion exchanger (AE) 1 - König, Jörg; et al. (Febs Letters, 1998)
The anion exchange protein AE1 is the most abundant membrane protein in human erythrocytes mediating the electroneutral chloride/bicarbonate exchange. We identified a promoter region in the 5' flanking region of the human AE1 gene which controls transcription in a cell type independent manner. In addition a second, distal promoter element mediates gene expression only in erythroid cells and in dependence upon differentiation. Within this distal promoter region we defined a 44 bp sequence containing a novel CT-rich motif with very strong promoter activity whereas a second 28 bp segment suppresses gene expression. Copyright (C) 1998 Federation of European Biochemical Societies.
Created from Fastlane, Scopus look-up
Keywords: Anion exchanger 1; Band 3; CT-rich region; Erythroid specific expression; Red blood cell maturation

Multidrug resistance protein-mediated transport of chlorambucil and melphalan conjugated to glutathione - König, Jörg; et al. (British Journal of Cancer, 1998)
The human multidrug resistance protein (MRP1) confers resistance of cells to a number of different cytostatic drugs and functions as an export pump for glutathione S-conjugates, glucuronides and other amphiphilic anions. The present study details for the first time MRP1-mediated ATP-dependent transport of various glutathione S-conjugates of the bifunctional alkylating agents chlorambucil and melphalan. In membrane vesicles prepared from cells expressing recombinant MRP1, the conjugates were transported at rates in the following order: monoglutathionyl chlorambucil > bisglutathionyl chlorambucil > monohydroxy monoglutathionyl chlorambucil and monoglutathionyl melphalan > monohydroxy monoglutathionyl melphalan. In addition, we show that membranes from chlorambucil-resistant GST-α-overexpressing CHO cells as well as from their parental cells express the hamster homologue of MRP1. With both CHO cell membrane preparations, we observed ATP-dependent transport of monoglutathionyl chlorambucil and of leukotriene C4, a glutathione S-conjugate and high-affinity substrate of MRP1. The transport rates measured in the resistant cells were only two- to three-fold higher than those measured in the control cells. These results together with cytotoxicity assays comparing MRP1-overexpressing cell pairs with the CHO cell pair indicate that, although MRP1-mediated transport is active, it may not be the rate-limiting step in chlorambucil resistance in these cell lines.
Created from Fastlane, Scopus look-up
Keywords: ATP-dependent transport; Chlorambucil; Glutathione S-conjugate; Melphalan; Multidrug resistance (-associated) protein (MRP1)

New Biomarkers for Renal Transporter-Mediated Drug–Drug Interactions: Metabolomic Effects of Cimetidine, Probenecid, Verapamil, and Rifampin in Humans - Geßner, Arne; König, Jörg; Wenisch, Pia; Heinrich, Markus; Stopfer, Peter; Fromm, Martin; Müller, Fabian (Clinical Pharmacology & Therapeutics, 2024)
The inhibition of renal transport proteins organic cation transporter 2 (OCT2), multidrug and toxin extrusion proteins (MATE1, MATE2-K), and organic anion transporters (OAT1, OAT3) causes clinically relevant drug–drug interactions (DDI). Endogenous biomarkers could be used to improve risk prediction of such renal DDIs. While a number of biomarkers for renal DDIs have been described so far, multiple criteria for valid biomarkers have frequently not been investigated, for example, specificity, metabolism, or food effects. Therefore, there is a need for novel biomarkers of renal DDIs. Here, we investigated the global metabolomic effects following the administration of two classical inhibitors of renal transport proteins [cimetidine (OCT2/MATEs), probenecid (OATs)] in human plasma and urine of healthy volunteers. Additionally, we investigated metabolomic effects of two inhibitors of other transporters [verapamil (P-glycoprotein), rifampin (organic anion transporting polypeptides)] as controls. This analysis shows that both cimetidine and probenecid affect compounds involved in caffeine metabolism, carnitines, and sulfates. Hierarchical cluster analysis of the effects of all four inhibitors on endogenous compounds identified multiple promising new sensitive and specific biomarker candidates for OCT2/MATE- or OAT-mediated DDIs. For OCT2/MATEs, 5-amino valeric acid betaine (median log2-fold change of estimated renal elimination: −3.62) presented itself as a promising candidate. For OATs, estimated renal elimination of 7-methyluric acid and cinnamoylglycine (median log2-fold changes −3.10 and −1.92, respectively) was both sensitive and specific. This study provides comprehensive information on metabolomic effects of transport protein inhibition in humans and identifies putative new sensitive and specific biomarkers for renal transporter-mediated DDIs.
CRIS-Team Scopus Importer:2024-08-23

Novel drug transporter substrates identification: An innovative approach based on metabolomic profiling, in silico ligand screening and biological validation - Nies, Anne T.; König, Jörg; Leuthold, Patrick; Damme, Katja; Winter, Stefan; Haag, Mathias; Masuda, Satohiro; Kruck, Stephan; Daniel, Hannelore; Spanier, Britta; Fromm, Martin; Bedke, Jens; et al. (Pharmacological Research, 2023)
Solute carrier (SLC) transport proteins are fundamental for the translocation of endogenous compounds and drugs across membranes, thus playing a critical role in disease susceptibility and drug response. Because only a limited number of transporter substrates are currently known, the function of a large number of SLC transporters is elusive. Here, we describe the proof-of-concept of a novel strategy to identify SLC transporter substrates exemplarily for the proton-coupled peptide transporter (PEPT) 2 (SLC15A2) and multidrug and toxin extrusion (MATE) 1 transporter (SLC47A1), which are important renal transporters of drug reabsorption and excretion, respectively. By combining metabolomic profiling of mice with genetically-disrupted transporters, in silico ligand screening and in vitro transport studies for experimental validation, we identified nucleobases and nucleoside-derived anticancer and antiviral agents (flucytosine, cytarabine, gemcitabine, capecitabine) as novel drug substrates of the MATE1 transporter. Our data confirms the successful applicability of this new approach for the identification of transporter substrates in general, which may prove particularly relevant in drug research.
CRIS-Team Scopus Importer:2023-10-06
Keywords: 5-Methylcytidine (PubChem CID: 92918); Anserine (PubChem CID: 112072); Capecitabine (PubChem CID: 60953); Cytarabine (PubChem CID: 6253); Cytosine (PubChem CID: 597); Drug screening; Drug transport; Flucytosine (PubChem CID: 3366); Gemcitabine (PubChem CID: 60750); In silico screening; Metabolomics; Multidrug and toxin extrusion protein 1; Proton-coupled peptide transporter 2

Phase I and II metabolism and MRP2-mediated export of bosentan in a MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 quadruple-transfected cell line - König, Jörg; Fahrmayr, Christina; Auge, Daniel; Mieth, Maren; Fromm, Martin; et al. (British Journal of Pharmacology, 2013)
Hepatic uptake (e.g. by OATP1B1), phase I and II metabolism (e.g. by CYP3A4, UGT1A1) and subsequent biliary excretion (e.g. by MRP2) are key determinants for the pharmacokinetics of numerous drugs. However, stably transfected cell models for the simultaneous investigation of transport and phase I and II metabolism of drugs are lacking. A newly established quadruple-transfected MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 cell line was used to investigate metabolism and transcellular transport of the endothelin receptor antagonist bosentan. Intracellular accumulation of bosentan equivalents (i.e. parent compound and metabolites) was significantly lower in all cell lines expressing MRP2 compared to cell lines lacking this transporter (P < 0.001). Accordingly, considerably higher amounts of bosentan equivalents were detectable in the apical compartments of cell lines with MRP2 expression (P < 0.001). HPLC and LC-MS measurements revealed that mainly unchanged bosentan accumulated in intracellular and apical compartments. Furthermore, the phase I metabolites Ro 48-5033 and Ro 47-8634 were detected intracellularly in cell lines expressing CYP3A4. Additionally, a direct glucuronide of bosentan could be identified intracellularly in cell lines expressing UGT1A1 and in the apical compartments of cell lines expressing UGT1A1 and MRP2. These in vitro data indicate that bosentan is a substrate of UGT1A1. Moreover, the efflux transporter MRP2 mediates export of bosentan and most likely also of bosentan glucuronide in the cell system. Taken together, cell lines simultaneously expressing transport proteins and metabolizing enzymes represent additional useful tools for the investigation of the interplay of transport and metabolism of drugs. BACKGROUND AND PURPOSE EXPERIMENTAL APPROACH KEY RESULTS CONCLUSIONS AND IMPLICATIONS

Role of Uptake Transporters OAT4, OATP2A1, and OATP1A2 in Human Placental Bio-disposition of Pravastatin - Fokina, Valentina M.; Patrikeeva, Svetlana; Wang, Xiao ming; Noguchi, Saki; Tomi, Masatoshi; König, Jörg; Ahmed, Mahmoud S.; Nanovskaya, Tatiana (Journal of Pharmaceutical Sciences, 2021)
Pravastatin is currently under evaluation for prevention of preeclampsia. Factors contributing to placental disposition of pravastatin are important in assessment of potential undesirable fetal effects. The purpose of this study was to identify the uptake transporters that contribute to the placental disposition of pravastatin. Our data revealed the expression of organic anion transporting polypeptide 1A2 (OATP1A2) and OATP2A1 in the apical, and OATP2B1 and OATP5A1 in the basolateral membranes of the placenta, while organic anion transporter 4 (OAT4) exhibited higher expression in basolateral membrane but was detected in both membranes. Preloading placental membrane vesicles with glutarate increased the uptake of pravastatin suggesting involvement of glutarate-dependent transporters such as OAT4. In the HEK293 cells overexpressing individual uptake transporters, OATP2A1, OATP1A2 and OAT4 were determined to accept pravastatin as a substrate at physiological pH, while the uptake of pravastatin by OATP2B1 (known to interact with pravastatin at acidic pH) and OATP5A1 was not detected at pH 7.4. These findings led us to propose that OATP1A2 and OATP2A1 are responsible for the placental uptake of pravastatin from the maternal circulation, while OAT4 mediates the passage of the drug across placental basolateral membrane in the fetal-to-maternal direction.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Drug transport; In vitro model; Kinetics; Membrane transport; Membrane transporters; Organic anion transporter(s); Organic anion transporting polypeptide(s); Placenta; Pregnancy; Transporter(s)

Screening of commonly prescribed drugs for effects on the CAT1-mediated transport of l-arginine and arginine derivatives - Banjarnahor, Sofna; König, Jörg; Maas, Renke (Amino Acids, 2022)
The cationic amino acid transporter 1 (CAT1/SLC7A1) plays a key role in the cellular uptake or export of l-arginine and some of its derivatives. This study investigated the effect of 113 chemically diverse and commonly used drugs (at 20 and 200 µM) on the CAT1-mediated cellular uptake of l-arginine, l-homoarginine, and asymmetric dimethylarginine (ADMA). Twenty-three (20%) of the tested substances showed weak inhibitory or stimulatory effects, but only verapamil showed consistent inhibitory effects on CAT1-mediated transport of all tested substrates.
CRIS-Team Scopus Importer:2022-04-15
Keywords: ADMA; CAT1; Inhibition; l-Arginine; l-Homoarginine

Solute Carrier Transporters as Potential Targets for the Treatment of Metabolic Disease - Schumann, Tina; König, Jörg; Henke, Christine; Willmes, Diana M.; Bornstein, Stefan R.; Jordan, Jens; Fromm, Martin; Birkenfeld, Andreas L. (Pharmacological reviews, 2020)
The solute carrier (SLC) superfamily comprises more than 400 transport proteins mediating the influx and efflux of substances such as ions, nucleotides, and sugars across biological membranes. Over 80 SLC transporters have been linked to human diseases, including obesity and type 2 diabetes (T2D). This observation highlights the importance of SLCs for human (patho)physiology. Yet, only a small number of SLC proteins are validated drug targets. The most recent drug class approved for the treatment of T2D targets sodium-glucose cotransporter 2, product of the SLC5A2 gene. There is great interest in identifying other SLC transporters as potential targets for the treatment of metabolic diseases. Finding better treatments will prove essential in future years, given the enormous personal and socioeconomic burden posed by more than 500 million patients with T2D by 2040 worldwide. In this review, we summarize the evidence for SLC transporters as target structures in metabolic disease. To this end, we identified SLC13A5/sodium-coupled citrate transporter, and recent proof-of-concept studies confirm its therapeutic potential in T2D and nonalcoholic fatty liver disease. Further SLC transporters were linked in multiple genome-wide association studies to T2D or related metabolic disorders. In addition to presenting better-characterized potential therapeutic targets, we discuss the likely unnoticed link between other SLC transporters and metabolic disease. Recognition of their potential may promote research on these proteins for future medical management of human metabolic diseases such as obesity, fatty liver disease, and T2D. SIGNIFICANCE STATEMENT: Given the fact that the prevalence of human metabolic diseases such as obesity and type 2 diabetes has dramatically risen, pharmacological intervention will be a key future approach to managing their burden and reducing mortality. In this review, we present the evidence for solute carrier (SLC) genes associated with human metabolic diseases and discuss the potential of SLC transporters as therapeutic target structures.
CRIS-Team Scopus Importer:2020-01-10

The human longevity gene homolog INDY and interleukin-6 interact in hepatic lipid metabolism - von Loeffelholz, Christian; Lieske, Stefanie; Neuschäfer-Rube, Frank; Willmes, Diana M.; Raschzok, Nathanael; Sauer, Igor M.; König, Jörg; Fromm, Martin; Horn, Paul; Chatzigeorgiou, Antonios; Pathe-Neuschäfer-Rube, Andrea; Jordan, Jens; et al. (Hepatology, 2017)
Reduced expression of the Indy ("I am Not Dead, Yet") gene in lower organisms promotes longevity in a manner akin to caloric restriction. Deletion of the mammalian homolog of Indy (mIndy, Slc13a5) encoding for a plasma membrane-associated citrate transporter expressed highly in the liver, protects mice from high-fat diet-induced and aging-induced obesity and hepatic fat accumulation through a mechanism resembling caloric restriction. We studied a possible role of mIndy in human hepatic fat metabolism. In obese, insulin-resistant patients with nonalcoholic fatty liver disease, hepatic mIndy expression was increased and mIndy expression was also independently associated with hepatic steatosis. In nonhuman primates, a 2-year high-fat, high-sucrose diet increased hepatic mIndy expression. Liver microarray analysis showed that high mIndy expression was associated with pathways involved in hepatic lipid metabolism and immunological processes. Interleukin-6 (IL-6) was identified as a regulator of mIndy by binding to its cognate receptor. Studies in human primary hepatocytes confirmed that IL-6 markedly induced mIndy transcription through the IL-6 receptor and activation of the transcription factor signal transducer and activator of transcription 3, and a putative start site of the human mIndy promoter was determined. Activation of the IL-6-signal transducer and activator of transcription 3 pathway stimulated mIndy expression, enhanced cytoplasmic citrate influx, and augmented hepatic lipogenesis in vivo. In contrast, deletion of mIndy completely prevented the stimulating effect of IL-6 on citrate uptake and reduced hepatic lipogenesis. These data show that mIndy is increased in liver of obese humans and nonhuman primates with NALFD. Moreover, our data identify mIndy as a target gene of IL-6 and determine novel functions of IL-6 through mINDY.Targeting human mINDY may have therapeutic potential in obese patients with nonalcoholic fatty liver disease. German Clinical Trials Register: DRKS00005450. (Hepatology 2017).
EVALuna2:8708

The Nonmetabolized β-Blocker Nadolol Is a Substrate of OCT1, OCT2, MATE1, MATE2-K, and P-Glycoprotein, but Not of OATP1B1 and OATP1B3 - Misaka, Shingen; Knop, Jana; Singer, Katrin; Hoier, Eva; Keiser, Markus; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2016)
Nadolol is a nonmetabolized ?-adrenoceptor antagonist and is a substrate of OATP1A2, but not of OATP2B1. However, other drug transporters involved in translocation of nadolol have not been characterized in detail. We therefore investigated nadolol as a potential substrate of the hepatic uptake transporters OATP1B1, OATP1B3, and OCT1 and of the renal transporters OCT2, MATE1, and MATE2-K expressed in HEK cells. Moreover, the importance of P-glycoprotein (P-gp) for nadolol transport was studied using double transfected MDCK-OCT1-P-gp cells. Nadolol was not transported by OATP1B1 and OATP1B3. In contrast, a significantly higher nadolol accumulation (at 1 and 10 ?M) was found in OCT1, OCT2, MATE1, and MATE2-K cells compared to control cells (P < 0.01). Km values for OCT2-, MATE1-, and MATE2-K-mediated nadolol uptake were 122, 531, and 372 ?M, respectively. Cimetidine (100 ?M, P < 0.01) and trimethoprim (100 ?M, P < 0.001) significantly inhibited OCT1-, OCT2-, MATE1-, and MATE2-K-mediated nadolol transport. The P-gp inhibitor zosuquidar significantly reduced basal to apical nadolol transport in monolayers of MDCK-OCT1-P-gp cells. In summary, nadolol is a substrate of the cation transporters OCT1, OCT2, MATE1, MATE2-K, and of P-gp. These data will aid future in vivo studies on potential transporter-mediated drug-drug or drug-food interactions with involvement of nadolol.
EVALuna2:8690

The prognostic biomarker L-homoarginine is a substrate of the cationic amino acid transporters CAT1, CAT2A and CAT2B - Chafai, Anja; Fromm, Martin; König, Jörg; Maas, Renke (Scientific Reports, 2017)
Low plasma concentration of L-homoarginine is an independent predictor of cardiovascular events and total mortality. Experimental data indicate that supplementation of L-homoarginine may have protective effects. We aimed to elucidate the mechanisms involved in the cellular uptake of L-homoarginine, which are little understood, so far. Using human embryonic kidney (HEK293) cell lines stably overexpressing the human cationic amino acid transporters CAT1 [solute carrier family 7 (SLC7A1)], CAT2A (SLC7A2A) or CAT2B (SLC7A2B) we assessed the transport kinetics of L-homoarginine and interactions with the CAT substrates L-arginine and asymmetric dimethylarginine (ADMA). Significant uptake of L-homoarginine was observed for all three CATs with apparent KM-values of 175 ± 7 µM for CAT1 and 523 ± 35 µM for CAT2B. Saturation of CAT2A-mediated L-homoarginine uptake could not be reached. Uptake of L-homoarginine by any of the three CATs could be inhibited by L-arginine and ADMA. Significant inhibition of CAT1-mediated uptake of L-homoarginine by L-arginine already occurred in the physiological concentration range. Taken together these data demonstrate that L-homoarginine is a substrate of CAT1, CAT2A and CAT2B and that CAT1 is a key site with regard to physiological relevance and interactions with related substrates such as L-arginine.
EVALuna2:32821

The renal transport protein OATP4C1 mediates uptake of the uremic toxin asymmetric dimethylarginine (ADMA) and efflux of cardioprotective L-homoarginine - Taghikhani, Emir Puyan; Maas, Renke; Fromm, Martin; König, Jörg (PLoS ONE, 2019)
Elevated plasma concentrations of the uremic toxin asymmetrical dimethylarginine (ADMA) and low plasma concentrations of L-homoarginine are independently associated with cardiovascular events and total mortality. Enzymes degrading ADMA [dimethylaminohydrolase 1 (DDAH1)] and synthesizing L-homoarginine [L-arginine:glycine amidinotransferase (AGAT)] are expressed in human proximal tubule cells. So far, it is not known which transport protein in the basolateral membrane of proximal tubule cells is mediating the uptake of ADMA into the cells for subsequent degradation or the export of intracellularly synthesized L-homoarginine. One study suggested that the uptake transporter OATP4C1 (gene symbol SLCO4C1) may be involved in the transport of ADMA and other uremic toxins. OATP4C1 is a member of the SLCO/SLC21 family of solute carriers, localized in the basolateral membrane of human proximal tubule cells. By using stably-transfected HEK cells overexpressing human OATP4C1, we demonstrate that ADMA and L-homoarginine are substrates of OATP4C1 with K-m values of 232.1 mu M and 49.9 mu M, respectively. ADMA and the structurally related uremic toxin SDMA (100 mu M) inhibited OATP4C1-mediated L-homoarginine uptake (P < 0.01), whereas other tested uremic toxins such as urea and p-cresyl sulfate have no effect on OATP4C1-mediated transport. Preloading experiments (300 mu M for 60 min) with subsequent efflux studies revealed that OATP4C1 also facilitates efflux e.g. of L-homoarginine. Both ADMA and L-homoarginine are substrates of human OATP4C1. Because proximal tubule cells are one site of ADMA metabolism and L-homoarginine synthesis, we postulate a protective role of OATP4C1 by mediating uptake of ADMA from and export of L-homoarginine into the systemic circulation.
CRIS-Team WoS Importer:2019-03-29

Transcriptional Regulation of Liver-Type OATP1B3 (Lt-OATP1B3) and Cancer-Type OATP1B3 (Ct-OATP1B3) Studied in Hepatocyte-Derived and Colon Cancer-Derived Cell Lines - Haberkorn, Bastian; Löwen, Dennis; Meier, Lukas; Fromm, Martin; König, Jörg (Pharmaceutics, 2023)
Due to alternative splicing, the SLCO1B3 gene encodes two protein variants; the hepatic uptake transporter liver-type OATP1B3 (Lt-OATP1B3) and the cancer-type OATP1B3 (Ct-OATP1B3) expressed in several cancerous tissues. There is limited information about the cell type-specific transcriptional regulation of both variants and about transcription factors regulating this differential expression. Therefore, we cloned DNA fragments from the promoter regions of the Lt-SLCO1B3 and the Ct-SLCO1B3 gene and investigated their luciferase activity in hepatocellular and colorectal cancer cell lines. Both promoters showed differences in their luciferase activity depending on the used cell lines. We identified the first 100 bp upstream of the transcriptional start site as the core promoter region of the Ct-SLCO1B3 gene. In silico predicted binding sites for the transcription factors ZKSCAN3, SOX9 and HNF1α localized within these fragments were further analyzed. The mutagenesis of the ZKSCAN3 binding site reduced the luciferase activity of the Ct-SLCO1B3 reporter gene construct in the colorectal cancer cell lines DLD1 and T84 to 29.9% and 14.3%, respectively. In contrast, using the liver-derived Hep3B cells, 71.6% residual activity could be measured. This indicates that the transcription factors ZKSCAN3 and SOX9 are important for the cell type-specific transcriptional regulation of the Ct-SLCO1B3 gene.
CRIS-Team Scopus Importer:2023-04-14
Keywords: colorectal carcinoma; Ct-OATP1B3; Ct-SLCO1B3; HNF1α; Lt-OATP1B3; Lt-SLCO1B3; SOX9; ZKSCAN3

Transporters and drug-drug interactions: important determinants of drug disposition and effects - König, Jörg; Fromm, Martin; Müller, Fabian (Pharmacological reviews, 2013)
Uptake and efflux transporters determine plasma and tissue concentrations of a broad variety of drugs. They are localized in organs such as small intestine, liver, and kidney, which are critical for drug absorption and elimination. Moreover, they can be found in important blood-tissue barriers such as the blood-brain barrier. Inhibition or induction of drug transporters by coadministered drugs can alter pharmacokinetics and pharmacodynamics of the victim drugs. This review will summarize in particular clinically observed drug-drug interactions attributable to inhibition or induction of intestinal export transporters [P-glycoprotein (P-gp), breast cancer resistance protein (BCRP)], to inhibition of hepatic uptake transporters [organic anion transporting polypeptides (OATPs)], or to inhibition of transporter-mediated [organic anion transporters (OATs), organic cation transporter 2 (OCT2), multidrug and toxin extrusion proteins (MATEs), P-gp] renal secretion of xenobiotics. Available data on the impact of nutrition on transport processes as well as genotype-dependent, transporter-mediated drug-drug interactions will be discussed. We will also present and discuss data on the variable extent to which information on the impact of transporters on drug disposition is included in summaries of product characteristics of selected countries (SPCs). Further work is required regarding a better understanding of the role of the drug metabolism-drug transport interplay for drug-drug interactions and on the extrapolation of in vitro findings to the in vivo (human) situation.

Transport of aromatic amino acids l-tryptophan, l-tyrosine, and l-phenylalanine by the organic anion transporting polypeptide (OATP) 3A1 - Surrer, Daniela; Schüsser, Sarah; König, Jörg; Fromm, Martin; Geßner, Arne (Febs Journal, 2024)
Amino acids are important for cellular metabolism. Their uptake across the plasma membrane is mediated by transport proteins. Despite the fact that the organic anion transporting polypeptide 4C1 (OATP4C1, Uniprot: Q6ZQN7) mediates transport of l-arginine and l-arginine derivatives, other members of the OATP family have not been characterized as amino acid transporters. The OATP family member OATP3A1 (gene symbol SLCO3A1, Uniprot: Q9UIG8) is ubiquitously expressed in human cells and highly expressed in many cancer tissues and cell lines. However, only a few substrates are known for OATP3A1. Accordingly, knowledge about its biological relevance is restricted. Our aim was to identify new substrates of OATP3A1 to gain insights into its (patho-)physiological function. In an LC-MS-based untargeted metabolomics assay using untreated OATP3A1-overexpressing HEK293 cells and control cells, we identified several amino acids as potential substrates of OATP3A1. Subsequent uptake experiments using exogenously added substrates revealed OATP3A1-mediated transport of l-tryptophan, l-tyrosine, and l-phenylalanine with 194.8 ± 28.7% (P < 0.05), 226.2 ± 18.7% (P < 0.001), and 235.2 ± 13.5% (P < 0.001), respectively, in OATP3A1-overexpressing cells compared to control cells. Furthermore, kinetic transport parameters (Km values) were determined (Trp = 61.5 ± 14.2 μm, Tyr = 220.8 ± 54.5 μm, Phe = 234.7 ± 20.6 μm). In summary, we identified the amino acids l-tryptophan, l-tyrosine, and l-phenylalanine as new substrates of OATP3A1. These findings could be used for a better understanding of (patho-)physiological processes involving increased demand of amino acids, where OATP3A1 should be considered as an important uptake transporter of l-tryptophan, l-tyrosine, and l-phenylalanine.
CRIS-Team Scopus Importer:2024-09-06
Keywords: amino acids; cancer; OATP3A1; transporter; tryptophan

Transport of Drugs and Endogenous Compounds Mediated by Human OCT1: Studies in Single- and Double-Transfected Cell Models - Haberkorn, Bastian; Fromm, Martin; König, Jörg (Frontiers in Pharmacology, 2021)
Organic Cation Transporter 1 (OCT1, gene symbol: SLC22A1) is predominately expressed in human liver, localized in the basolateral membrane of hepatocytes and facilitates the uptake of endogenous compounds (e.g. serotonin, acetylcholine, thiamine), and widely prescribed drugs (e.g. metformin, fenoterol, morphine). Furthermore, exogenous compounds such as MPP+, ASP(+) and Tetraethylammonium can be used as prototypic substrates to study the OCT1-mediated transport in vitro. Single-transfected cell lines recombinantly overexpressing OCT1 (e.g., HEK-OCT1) were established to study OCT1-mediated uptake and to evaluate transporter-mediated drug-drug interactions in vitro. Furthermore, double-transfected cell models simultaneously overexpressing basolaterally localized OCT1 together with an apically localized export protein have been established. Most of these cell models are based on polarized grown MDCK cells and can be used to analyze transcellular transport, mimicking the transport processes e.g. during the hepatobiliary elimination of drugs. Multidrug and toxin extrusion protein 1 (MATE1, gene symbol: SLC47A1) and the ATP-driven efflux pump P-glycoprotein (P-gp, gene symbol: ABCB1) are both expressed in the canalicular membrane of human hepatocytes and are described as transporters of organic cations. OCT1 and MATE1 have an overlapping substrate spectrum, indicating an important interplay of both transport proteins during the hepatobiliary elimination of drugs. Due to the important role of OCT1 for the transport of endogenous compounds and drugs, in vitro cell systems are important for the determination of the substrate spectrum of OCT1, the understanding of the molecular mechanisms of polarized transport, and the investigation of potential drug-drug interactions. Therefore, the aim of this review article is to summarize the current knowledge on cell systems recombinantly overexpressing human OCT1.
CRIS-Team WoS Importer:2021-05-14

Transport of L-Arginine Related Cardiovascular Risk Markers - Banjarnahor, Sofna; Rodionov, Roman N.; König, Jörg; Maas, Renke (Journal of Clinical Medicine, 2020)
L-arginine and its derivatives, asymmetric and symmetric dimethylarginine (ADMA and SDMA) and L-homoarginine, have emerged as cardiovascular biomarkers linked to cardiovascular outcomes and various metabolic and functional pathways such as NO-mediated endothelial function. Cellular uptake and efflux of L-arginine and its derivatives are facilitated by transport proteins. In this respect the cationic amino acid transporters CAT1 and CAT2 (SLC7A1 and SLC7A2) and the system y(+)L amino acid transporters (SLC7A6 and SLC7A7) have been most extensively investigated, so far, but the number of transporters shown to mediate the transport of L-arginine and its derivatives is constantly increasing. In the present review we assess the growing body of evidence regarding the function, expression, and clinical relevance of these transporters and their possible relation to cardiovascular diseases.
CRIS-Team WoS Importer:2021-01-15

Tropane alkaloids as substrates and inhibitors of human organic cation transporters of the SLC22 (OCT) and the SLC47 (MATE) families - Chen, Jiayin; Brockmoeller, Juergen; Seitz, Tina; König, Jörg; Tzvetkov, Mladen V.; Chen, Xijing (Biological Chemistry, 2017)
Tropane alkaloids and their derivatives are anticholinergic drugs with narrow therapeutic range. Here we characterize the organic cation transporters from the SLC22 (OCT1, OCT2, and OCT3) and the SLC47 families (MATE1 and MATE2-K) as potential mediators of the renal and extra-renal excretion, the two major roads of elimination of these substances. All analyzed compounds inhibited and the quaternary amine derivatives ipratropium and trospium were strongly transported by OCTs and MATEs. Overexpression of OCTs or MATEs in HEK293 cells resulted in an up to 63-fold increase in the uptake of ipratropium (Km of 0.32 ?m to OCT2 and Vmax of 3.34 nmol×mg protein-1×min-1 to MATE1). The transcellular transport of ipratropium was 16-fold higher in OCT2-MATE1 and 10-fold higher in OCT1-MATE1 overexpressing compared to control MDCKII cells. Genetic polymorphisms in OCT1 and OCT2 affected ipratropium uptake and clinically relevant concentration of ondansetron and pyrithiamine inhibited ipratropium uptake via MATEs by more than 90%. This study suggests that OCT1, OCT2 and MATEs may be strongly involved in the renal and extra-renal elimination of ipratropium and other quaternary amine alkaloids. These substances have a notoriously narrow therapeutic range and the drug-drug interactions suggested here should be further critically evaluated in humans.
EVALuna2:8707

Vectorial transport of the arginine derivatives asymmetric dimethylarginine (ADMA) andl-homoarginine by OATP4C1 and P-glycoprotein studied in double-transfected MDCK cells - Taghikhani, Emir Puyan; Maas, Renke; Taudte, Verena; Geßner, Arne; Fromm, Martin; König, Jörg (Amino Acids, 2020)
Elevated plasma concentrations of the uremic toxin asymmetric dimethylarginine (ADMA) and low plasma concentrations ofl-homoarginine are independently associated with cardiovascular events and mortality. Key enzymes involved in the homeostasis of both arginine derivatives are expressed in proximal tubule cells of the kidney. To get access to these enzymes, transport proteins are important. One of the transporters mediating the transport of ADMA andl-homoarginine is the solute carrier superfamily (SLC) member OATP4C1, located in the basolateral membrane of proximal tubule cells. To gain insights into the role of export pumps in the transport of both substances, we established a double-transfected MDCK cell line expressing OATP4C1 and the export pump P-glycoprotein (P-gp). Using MDCK cell monolayers, we demonstrated in time-dependent and concentration-dependent vectorial transport experiments that ADMA andl-homoarginine are transported from the basolateral to the apical compartment of MDCK-OATP4C1-P-gp cells with significantly higher transport rates compared to single-transfected MDCK-OATP4C1, MDCK-P-gp and MDCK-VC (control) cells (e.g. transport ratio MDCK-OATP4C1-P-gp/MDCK-VC: for 50 mu M ADMA = 2.0-fold, for 50 mu Ml-homoarginine = 3.4-fold). These results indicate that both OATP4C1 and P-gp transport the arginine derivatives ADMA andl-homoarginine and are, therefore, important for the homoeostasis of both substances.
CRIS-Team WoS Importer:2020-07-17

Zebrafish Oatp1d1 Acts as a Cellular Efflux Transporter of the Anionic Herbicide Bromoxynil - Halbach, Katharina; Aulhorn, Silke; Lechtenfeld, Oliver Jens; Lecluse, Marion; Leippe, Sophia; Reemtsma, Thorsten; Seiwert, Bettina; Wagner, Stephan; König, Jörg; Luckenbach, Till (Chemical Research in Toxicology, 2022)
Toxicokinetics (TK) of ionic compounds in the toxico-/pharmacological model zebrafish embryo (Danio rerio) depend on absorption, distribution, metabolism, and elimination (ADME) processes. Previous research indicated involvement of transport proteins in the TK of the anionic pesticide bromoxynil in zebrafish embryos. We here explored the interaction of bromoxynil with the organic anion-transporting polypeptide zebrafish Oatp1d1. Mass spectrometry imaging revealed accumulation of bromoxynil in the gastrointestinal tract of zebrafish embryos, a tissue known to express Oatp1d1. In contrast to the Oatp1d1 reference substrate bromosulfophthalein (BSP), which is actively taken up by transfected HEK293 cells overexpressing zebrafish Oatp1d1, those cells accumulated less bromoxynil than empty vector-transfected control cells. This indicates cellular efflux of bromoxynil by Oatp1d1. This was also seen for diclofenac but not for carbamazepine, examined for comparison. Correspondingly, internal concentrations of bromoxynil and diclofenac in the zebrafish embryo were increased when coexposed with BSP, inhibiting the activities of various transporter proteins, including Oatp1d1. The effect of BSP on accumulation of bromoxynil and diclofenac was enhanced in further advanced embryo stages, indicating increased efflux activity in those stages. An action of Oatp1d1 as an efflux transporter of ionic environmental compounds in zebrafish embryos should be considered in future TK assessments.
CRIS-Team WoS Importer:2022-01-21